Monitoring the activity of 2-oxoglutarate dependent histone demethylases by NMR spectroscopy: direct observation of formaldehyde. - Hopkinson, R; Hamed, R; Rose, N; Claridge, T; Schofield, C (2010)
(Chemical Equation Presented) Formaldetected: Application of 1H- and 1D 13C HSQC NMR spectroscopy methods for monitoring the activity of a 2-oxoglutarate dependent histone Nε-emethyllysine demethylase (JMJD2E) enabled the in situ quantitative analysis of the different components of the reaction, including the direct observation of hydrated formaldehyde resulting from enzyme-catalysed demethylation. © 2010 Wiley-VCH Verlag GmbHand Co. KGaA.